Low-dose fludarabine and cyclophosphamide combined with rituximab in the first-line treatment of elderly/comorbid patients with chronic lymphocytic leukaemia/small lymphocytic lymphoma (CLL/SLL): long-term results of project Q-lite by the Czech CLL Study Group - Smolej, Lukáš; Brychtová, Yvona; Cmunt, Eduard; Doubek, Michael; Špaček, Martin; Belada, David; Šimkovič, Martin; Stejskal, Lukáš; Zygulová, Irena; Urbanová, Renata; Brejcha, Martin; Zuchnická, Jana; et al. (British journal of haematology, 2021)
Therapeutic options used to be very limited for treatment-naïve elderly/comorbid patients with chronic lymphocytic leukaemia/small lymphocytic lymphoma (CLL/SLL) before the introduction of chemo-immunotherapy. Because dose-reduced fludarabine-based regimens yielded promising results, the Czech CLL Study Group initiated a prospective observational study to assess safety and efficacy of low-dose fludarabine and cyclophosphamide combined with rituximab (FCR) in elderly/comorbid patients. Between March 2009 and July 2012, we enrolled 107 patients considered ineligible for full-dose FCR (median age, 70 years; median Cumulative Illness Rating Scale score, 5; median creatinine clearance, 69 ml/min). Notably, 77% patients had unfavourable biological prognosis [unmutated immunoglobulin heavy-chain variable-region gene (IGHV), 74%; deletion 17p, 9%). Fludarabine was reduced to 12 mg/m2 intravenously (iv) or 20 mg/m2 orally on days 1-3 and cyclophosphamide to 150 mg/m2 iv/orally on days 1-3. Grade 3-4 neutropenia occurred in 56% of the patients, but there were serious infections in only 15%. The median progression-free survival was 29 months, but was markedly longer in patients with mutated IGHV (median 53 months), especially in absence of del 11q or 17p (median 74 months). Low-dose FCR is a well-tolerated and effective first-line regimen for selected elderly/comorbid patients with CLL/SLL with favourable biology. The study was registered at clinicaltrials.gov (NCT02156726).
Keywords: comorbidity; Cyclophosphamide; low-dose FCR; Female; ženské pohlaví; Vidarabine; Leukemia, Lymphocytic, Chronic, B-Cell; přežití bez známek nemoci; lidé; Rituximab; následné studie; míra přežití; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Follow-Up Studies; Male; Aged; Czech Republic; rituximab; Survival Rate; Česká republika; vidarabin; Disease-Free Survival; fludarabine; senioři; mužské pohlaví; chronic lymphocytic leukaemia; cyklofosfamid; chronická lymfatická leukemie; Humans